Potestas nocendi w świetle komentarzy św. Augustyna do Księgi Hioba 1-2 - Terka, Mariusz (Vox Patrum, 2016)
St. Augustine interprets the tragedy of Job presented in the Bible by two coincidental and connected with each other scenes: the first describes the history of man depressed with suffering, who lost his property, family and health, where the second one shows the dialog on the spiritual level between God and Satan, in consequence of which Satan receives the power of doing damage (potestas nocendi) to Job. The matter of this power, its range and goal are examined by The Bishop of Hippo by means of the relationship analysis between God, deviland Job. The power of harming comes from God and He is definitely responsible for Job’s suffering. He gives this power for devil but only for making man more prefect and revealing His justice. Where the action of devil is the charge of insincere devotion, jealousy, suspecting of hidden sin and temptation of Job in order to make him turn around from God. But for Job the experience of suffering is the trial which is given from God and by it God demands from Job taking a decision. His reply to God is described by St. Augustine as trust and agreement his will with God’s will. The power of harming is limited first by God’s will and permission given by Him, next by devil’s nature as a creature which has to ask for harming permission and hasn’t got any access to human heart, and later by Job’s will and a choice made by him. So potestas nocendi is not license of devil, but first of all the power of God and devil’s desire of harming.